Mechanics of the canine femur with two types of hip replacement stems - Shahar, R.; Banks-Sills, L.; Eliasy, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The long-term performance of total hip replacement is of concern to veterinary surgeons. Two of the main complications associated with this procedure are implant loosening and stress shielding. Designs of the femoral stem which will avoid loosening and achieve maximum endurance while reducing stress shielding and periprosthetic bone loss are sought.In the intact femur the stress is distributed over the entire cross section of the bone. After hip replacement this pattern of stress distribution is altered because of the manner in which the load is transferred from the prosthesis to the bone.The objective of this study was to examine the stresses that develop in the femur and implant components of two different methods of hip replacement used clinically in dogs. Anatomic, three-dimensional finite element models of the canine femur with a cemented femoral stem and a Zurich cementless stem were constructed. The stresses and displacements were calculated by the finite element analysis method, under physiologic loads that included muscle forces and joint reaction forces. The results were compared to results obtained by a similar analysis of an intact femur.This study demonstrates that the Zurich cementless method causes less stress shielding in the proximal femoral cortex than does the cemented method. Implant stresses are higher in the Zurich cementless stem, but still within an acceptable range.
Keywords: Finite element; femur; hip replacement